Occupational Risk Analysis in the Work Environment of Health Centers and Its Role in Improving Treatment Quality: An Applied Study at the First Clinic Center (The International Journal for Scientific Research, 2024)
This study aims to analyze occupational hazards in healthcare centers and assess their impact on treatment quality at the First Clinic Center. Using an analytical approach, key hazards, including chemical, biological, physical, and psychological risks, were identified, and the effectiveness of current preventive measures was evaluated. The findings indicate that continuous training and promoting a culture of occupational safety are crucial for improving risk management and reducing their negative impact on healthcare quality. Additionally, the study highlights the need for better workplace design to minimize physical risks and enhance interdepartmental cooperation within the center. Based on these findings, practical recommendations were developed, including enhancing continuous training programs, improving safety procedures, and providing psychological and social support for workers. These recommendations aim to achieve a better balance between occupational safety and work efficiency, thereby improving the quality of healthcare services and the health and safety of both workers and patients.
Keywords: Occupational Risks; Treatment Quality; Occupational Safety; Continuous Training; Work Environment